Effects of hyperbaric oxygen therapy on autistic behaviors and GRIN2B gene expression in valproic acid-exposed rats - Mohtaj Khorassani, Yalda; Moghimi, Ali; Khakzad, Mohammad Reza; Fereidoni, Masoud; Hassani, Delaram; Torbati Gah, Javad (Frontiers in Neuroscience, 2024)
Autism is a complex neurodevelopmental condition characterized by deficits in social interaction, communication, and restricted repetitive behaviors. Hyperbaric oxygen therapy (HBOT) has emerged as a potential treatment for autism, although its effects on behavior and gene expression are not well understood. The GRIN2B gene, known for its involvement in encoding a glutamate receptor subunit crucial for neuron communication and associated with autism, was a focus of this study. Using a rat model induced by prenatal exposure to valproic acid, we examined the impact of HBOT on autism-like behaviors and GRIN2B gene expression. Male Wistar rats were categorized into four groups: control, VPA (valproic acid-exposed), VPA+HBOT (2 atmosphere absolute (ATA)), and VPA+HBOT (2.5 ATA). The rats underwent several behavioral tests to assess social behavior, anxiety, stereotype and exploratory behaviors, and learning. Following the behavioral tests, the HBOT groups received 15 sessions of HBOT at pressures of 2 and 2.5 (ATA), and their behaviors were re-evaluated. Subsequently, real-time PCR was employed to measure GRIN2B gene expression in the frontal lobe. A significance level of p-value ≤ 0.05 was considered in all the statistical analysis. Our results indicated that HBOT significantly increased social interaction and exploratory behaviors in VPA-exposed rats, alongside elevated GRIN2B gene expression in their frontal lobe. A significance level of p-value ≤ 0.05 was considered in all the statistical analysis. Our findings imply that HBOT might have a potential role in ameliorating autism-related behaviors in the VPA rat model of autism through potential modulation of GRIN2B gene expression. However, additional research is essential to fully comprehend the underlying mechanisms and refine the HBOT protocol for optimizing its effectiveness in improving autism-related symptoms.